Research on the stability of the 3D frame on coral foundation subjected to impact load - Hung, Nguyen Thanh; Chung, Nguyen Thai; Luong, Hoang Xuan (Vietnam Journal of Marine Science and Technology, 2020)
This article presents an application of the finite element method (FEM) for the stability analysis of 3D frame (space bar system) on the coral foundation impacted by collision impulse. One-way joints between the rod and the coral foundation are described by the contact element. Numerical analysis shows the effect of some factors on the stability of the bar system on coral foundation. The results of this study can be used for stability analysis of the bar system on coral foundation subjected to sea wave load.